2004
DOI: 10.1002/pmic.200300783
|View full text |Cite
|
Sign up to set email alerts
|

N‐Terminal myristoylation predictions by ensembles of neural networks

Abstract: N-terminal myristoylation is a post-translational modification that causes the addition of a myristate to a glycine in the N-terminal end of the amino acid chain. This work presents neural network (NN) models that learn to discriminate myristoylated and nonmyristoylated proteins. Ensembles of 25 NNs and decision trees were trained on 390 positive sequences and 327 negative sequences. Experiments showed that NN ensembles were more accurate than decision tree ensembles. Our NN predictor evaluated by the leave-on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
161
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(163 citation statements)
references
References 12 publications
0
161
0
Order By: Relevance
“…For post-translational modifications, we looked for GPI anchors (http://mendel.imp.ac.at/sat/gpi/gpi_server. html) 53 , myristoylation (http://web.expasy.org/myristoylator/) 54 , palmitoylation (http://csspalm.biocuckoo.org/) 55 and prenylation (http://mendel.imp.ac.at/sat/ PrePS/index.html) 56 .…”
Section: Methodsmentioning
confidence: 99%
“…For post-translational modifications, we looked for GPI anchors (http://mendel.imp.ac.at/sat/gpi/gpi_server. html) 53 , myristoylation (http://web.expasy.org/myristoylator/) 54 , palmitoylation (http://csspalm.biocuckoo.org/) 55 and prenylation (http://mendel.imp.ac.at/sat/ PrePS/index.html) 56 .…”
Section: Methodsmentioning
confidence: 99%
“…Since we showed that the myristoylation of short chimeric WT-ctPAK2-N 15 -EGFP and WT-Yes-N 11 -GFP can readily be detected using azidomyristate cell labeling and reaction with phosphinebiotin (Fig. 2), we first identified internal myristoylation sites adjacent to caspase cleavage sites using computational prediction analysis (23,24) and, second, incorporated these predicted NMT substrate sequences at the N terminus of EGFP at the cDNA level (Supplemental Table 2). Finally, using our nonradioactive azidomyristate labeling/ phosphine-biotin-based detection method, we assessed the myristoylation status of the chimeric EGFP proteins transiently expressed in COS-7 cells.…”
Section: Discussionmentioning
confidence: 99%
“…To do so, the complete carboxyl terminal sequences downstream of the caspase cleavage site were subjected to computational prediction analysis based on myristoylator and NMT-the Myr Predictor algorithms (23,24). Of more than 280 proteins identified as caspase substrates (22), 48 occurred immediately upstream of a glycine residue, and 9 of these proteins received favorable scores for myristoylation and were identified as putative candidates for post-translational myristoylation (Supplemental Table 2).…”
Section: Development Of a Strategy For The Rapid Identification Of Pomentioning
confidence: 99%
“…2 Unlike most Arfs, they are not N-terminally myristoylated even though the glycine residue at position 2 is highly conserved between organisms, but the serine at position 6 important for myristoylation is missing. 3 However they do fit into the Arf subfamily of the Ras superfamily because the structural analysis has shown that both Arl2 and Arl3 display the very dramatic conformational change between the GDP-and the GTP-bound conformations, whereby the first 2 strands of the b-sheet, also called the interswitch toggle, move by 2 residues along the rest of the sheet. 4 Both proteins also have an N-terminal amphiphatic helix characteristic for the Arf subfamily.…”
Section: The Similarity Between Arl2 and Arl3mentioning
confidence: 99%